S.A. Yesenin in the English-Speaking World: New and Little-Known Facts - Svetlana A. Seregina (Studia Litterarum)
The article introduces materials hitherto unknown in the Russian academia: (1) the first characteristic of Sergey Yesenin in English (together with the Russian translation), given by Avrahm C. Yarmolinsky in his anthology Modern Russian Poetry. An anthology, Chosen and Translated by Babette Deutsch and Avrahm Yarmolinsky (New York: Harcourt, Brace and Co., 1921); a historical and literary inquiry about S.A. Yesenin, which A.C. Yarmolinsky presents in his book A Treasure of Russian Verse (New York, 1949); (2) the translation of the third chapter of Yesenin’s poem Transfiguration made in 1926 by A. Kaun and R. Holloway and published in November 1926 in the Chicago- based magazine Роetry. The article compares two versions of the translation of the third chapter of Transfiguration: the earlier translation by A. Yarmolinsky and B. Deutsch and the later one by A. Kaun and R. Holloway. We come to the following conclusion: Kaun and Holloway knew the translation made by Yarmolinsky and Deutsch took it into account when preparing their own. However, their translation is more accurate to the original text and is stylistically superior: Kaun and Holloway were able to keep the evangelic references of the original poem as well as its mythopoetic pathos. Kaun and Holloway were better translators as they were able to render Yesenin’s poem more accurately.